UNESCO: A historical study of its genesis and tasks 1945-1948 (Journal of the College of Basic Education, 2023)
UNESCO is the well-known term for the United Nations Educational, Scientific and Cultural Organization, which is a specialized agency of the United Nations, founded in 1945 at the end of the Second World War. The development of international contributions in the fields of education, science and culture, so UNESCO is developing the values of universal respect for justice, the rule of law, human rights and fundamental freedoms that were approved in the United Nations list, so the research was divided into three sections. The second is on the organs of UNESCO and its sources of funding, and the third topic is concerned with studying the activities, fields and tasks of the UNESCO.